FISHERS AND FISHERIES: ISSUES OF SUSTAINABLE RESOURCE EXPLOITATION. A CASE STUDY OF BONNY AREA IN NIGERIA - ABOHWEYERE, P. O; ANYANWU, A. O.; JIM-SAIKI, L. O.; ABIOLA, T.K.; OGUNBADEJO, K.H.; ALHAJI, T.A.; WILLIAMS, A. B.; ESEWANE, G.N.; ADEOGUN, O. A.; GBOLAGUN, A.; ARORIODE, R. O. (Nigerian Journal of Fisheries, 2011)
Fishers from four river systems, Bonny, New Calabar, Sombreiro and Andoni in Bonny area of Niger Delta were identified. A characteristic of fishers, being a very mobile group was evident from the total of 10 ethnic groups identified, five of which were not indigenous to the area. Age structure ranged from <10 to 74 years. Seven main fisheries exploited were big fish, catfish, shrimp, croaker, sardine and shark. Thirteen different gear types used in the exploitation of the fishery ranged from gill nets of various mesh size, hand and purse seines, and hook and lines; eight were passive and five active. The fisheries resources were exploited within eight fishing grounds in Rivers (Bonny, New Calabar, Sombreiro and Andoni) and in creeks, estuaries and the Atlantic Ocean off these river systems. Estimated CPUE showed highest average from the Ocean fishing grounds with lowest values being obtained from rivers and creeks. Exploitation strategies employing higher number of passive gears, and allowing escape of smaller sizes of fish coupled with highest average CPUE from the Atlantic Ocean fishing grounds where larger sizes were found, are significant for resource sustainability. Encountered exploitation strategies were in compliance with the dictates of responsible fisheries which is being advocated for sustainability of all fisheries resources globally.